Role of KIR3DS1 in human diseases - Kӧrner, Christian; Altfeld, Marcus (Frontiers in Immunology, 2012)
The function of NK cells is controlled by several activating and inhibitory receptors, including the family of Killer-immunoglobulin-like receptors (KIRs). The KIR gene 3DS1 (KIR3DS1) represents a conserved allelic variant of the KIR3DL1/S1 gene locus. 3DS1 belongs to the KIR haplotype group B along with other KIR genes encoding for activating KIRs and is present in all human populations. The encoded gene product KIR3DS1 exhibits three extracellular domains, a short cytoplasmic tail and a trans-membrane domain containing a positively charged residue. The latter allows recruitment of the ITAM-bearing adaptor molecule, DAP12, and thus conferring the activating quality to KIR3DS1. Although interaction with its putative ligand HLA-Bw4-I80 or any other HLA class I subtype has not been demonstrated to date, a growing number of associations between the presence of 3DS1 and the outcome of viral infections have been described. Especially, the protective role of KIR3DS1 in combination with HLA-Bw4-I80 in the context of progressive HIV infection has been studied intensively. In addition, a number of recent studies associated the presence or absence of KIR3DS1 with the occurrence and outcome of several malignancies, as well as of autoimmune diseases and graft-versus-host disease (GVHD). In this review, the present knowledge regarding the role of KIRD3S1 in various diseases will be summarized.